Acute kidney injury in patients with COVID-19 compared to those with influenza: a systematic review and meta-analysis - Hsiao, Chiu-Ying; Pan, Heng-Chih; Wu, Vin-Cent; Su, Ching-Chun; Yeh, Tzu-Hsuan; Chuang, Min-Hsiang; Tu, Kuan-Chieh; Wang, Hsien-Yi; Kan, Wei-Chih; Yang, Chun-Chi; Chen, Jui-Yi (Frontiers in Medicine, 2023)
Background: COVID-19 and influenza can both lead to acute kidney injury (AKI) as a common complication. However, no meta-analysis has been conducted to directly compare the incidence of AKI between hospitalized patients with COVID-19 and influenza. The objective of our study aims to investigate the incidence and outcomes of AKI among hospitalized patients between these two groups. Material and Methods: A systematic search of PubMed, Embase, and Cochrane databases was conducted from December 2019 to February 2022 to identify studies examining AKI and clinical outcomes among hospitalized patients with COVID-19 and influenza. The primary outcome of interest was the incidence of AKI, while secondary outcomes included in-hospital mortality, recovery from AKI, hospital and ICU stay duration. The quality of evidence was evaluated using Cochrane and GRADE methods. Results: Twelve retrospective cohort studies, involving 17,618 hospitalized patients with COVID-19 and influenza, were analyzed. COVID-19 patients showed higher AKI incidence (29.37% vs 20.98%, OR: 1.67, 95% CI 1.56-1.80, p < 0.01, I2 = 92.42%), and in-hospital mortality (30.95% vs. 5.51%, OR: 8.16, 95% CI 6.17-10.80, p < 0.01, I2 = 84.92%) compared to influenza patients with AKI. Recovery from AKI was lower in COVID-19 patients (57.02% vs, 80.23%, OR: 0.33, 95% CI 0.27-0.40, p < 0.01, I2 = 85.17%). COVID-19 patients also had a longer hospital stay (SMD: 0.69, 95% CI 0.65-0.72, p < 0.01, I2 = 98.94%) and longer ICU stay (SMD: 0.61, 95% CI 0.50-0.73, p < 0.01, I2 = 94.80%) than influenza patients. In our study, evidence quality was high (NOS score 7-9), with low certainty for AKI incidence and moderate certainty for recovery form AKI by GRADE assessment. Conclusion: COVID-19 patients had higher risk of developing AKI, experiencing in-hospital mortality, and enduring prolonged hospital/ICU stays in comparison to influenza patients. Additionally, the likelihood of AKI recovery was lower among COVID-19 patients.